China in light of the performance of Central and East European economies - Jan Svejnar (Institute for the Study of Labor (IZA), 2007)
While China shared many systemic, initial conditions with the transition economies of Central-East Europe (CEE) and the Commonwealth of Independent States (CIS), it had a more agricultural economy and a more stable political-economic system than many CEE and CIS countries. Unlike most of the CEE and CIS economies, China adopted a strategy of gradual economic transformation that maintained the existing system and created new economic activities on top of it. This enabled China to avoid the transformation depression observed in CEE and CIS, and allowed it to generate high rates of economic growth that have now lasted for almost three decades. At the time of this study, the CEE and CIS economies have also completed a decade or more of respectable economic growth, demonstrating that numerous forms of the transition process can generate long term economic growth. In retrospect, the tradeoff for avoiding an initial depression appears to be the willingness to maintain most of the existing economic and political system rather than embarking on a rapid but incomplete economic and political transformation. With a rising economic instability and political pressure, countries such as Poland and the Soviet Union (CIS) had little choice but to proceed relatively fast. Others, such as East Germany and Czechoslovakia, could have retained the centrally planned system, but they abandoned it and communism rapidly for political reasons. Looking forward, the current situation is an optimistic one, with China, CIS and CEE belonging to the fastest growing regions of the world. It will be interesting to see whether all or only some of these models will turn out to be successful in the long run.
urn:nbn:de:101:1-20080401398
Keywords: 330; Übergangswirtschaft; Systemtransformation; Wirtschaftskrise; Wirtschaftswachstum; Vergleich; China; Osteuropa; GUS-Staaten